2021
DOI: 10.1038/s41598-021-99323-8
|View full text |Cite
|
Sign up to set email alerts
|

Pilot investigation on the dose-dependent impact of irradiation on primary human alveolar osteoblasts in vitro

Abstract: Radiotherapy of head and neck squamous cell carcinoma can lead to long-term complications like osteoradionecrosis, resulting in severe impairment of the jawbone. Current standard procedures require a 6-month wait after irradiation before dental reconstruction can begin. A comprehensive characterization of the irradiation-induced molecular and functional changes in bone cells could allow the development of novel strategies for an earlier successful dental reconstruction in patients treated by radiotherapy. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Szymczyk et al [ 9 ] showed that the decrease in cell proliferation was due to cell death induction by the radiation caused by G2 cell cycle arrest and the resulting enhanced sensitivity to apoptotic factors. Amler et al [ 11 ] isolated human alveolar osteoblasts and expanded them into cell lines. These cell lines were irradiated with single fractions of 2, 6, or 10 Gy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Szymczyk et al [ 9 ] showed that the decrease in cell proliferation was due to cell death induction by the radiation caused by G2 cell cycle arrest and the resulting enhanced sensitivity to apoptotic factors. Amler et al [ 11 ] isolated human alveolar osteoblasts and expanded them into cell lines. These cell lines were irradiated with single fractions of 2, 6, or 10 Gy.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies show that higher doses of RT decrease osteoblast function and viability [7][8][9][10][11]. For example, Matsumura et al [7] exposed the osteoblast-like cell line, MC3T3-E1, to doses of 1, 5, and the mineralized matrix of the bone.…”
Section: ) Osteoblastsmentioning
confidence: 99%
“…Osteoblasts are highly sensitive to ionizing radiation. The growth, survival, and functional maturation of osteoblasts are markedly suppressed when the bone is exposed to radiation ( 14 , 15 ). Osteoblasts are also much more vulnerable to ionizing radiation than undifferentiated mesenchymal stem cells ( 16 ).…”
Section: Introductionmentioning
confidence: 99%